2012
DOI: 10.1021/ml3000325
|View full text |Cite
|
Sign up to set email alerts
|

Design of a Potent CB1 Receptor Antagonist Series: Potential Scaffold for Peripherally-Targeted Agents

Abstract: Antagonism of cannabinoid-1 (CB 1 ) receptor signaling has been demonstrated to inhibit feeding behaviors in humans, but CB 1 -mediated central nervous system (CNS) side effects have halted the marketing and further development of the lead drugs against this target. However, peripherally restricted CB 1 receptor antagonists may hold potential for providing the desired efficacy with reduced CNS side effect profiles. In this report we detail the discovery and structure−activity-relationship analysis of a novel b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(13 citation statements)
references
References 23 publications
0
13
0
Order By: Relevance
“…Previous studies have revealed that peripheral cannabinoid CB1 receptor blockage is sufficient enough to suppress food intake 26 , increase energy expenditure and reduce lipogenesis in both liver and adipose tissues 27 , 28 . A number of scaffolds especially diaryl heterocyclic compounds such as pyrazoles 34 38 , pyrroles 39 , 40 , pyrazolines 41 , 42 , purines 43 , 44 , tetrahydroindazoles 45 , tetrahydropyrazolo[4,3- c ]pyridines 46 etc. have been tried as CB1 receptor antagonists acting peripherally with lower CNS side effects but, unfortunately none of these compounds could make it to the market till date.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have revealed that peripheral cannabinoid CB1 receptor blockage is sufficient enough to suppress food intake 26 , increase energy expenditure and reduce lipogenesis in both liver and adipose tissues 27 , 28 . A number of scaffolds especially diaryl heterocyclic compounds such as pyrazoles 34 38 , pyrroles 39 , 40 , pyrazolines 41 , 42 , purines 43 , 44 , tetrahydroindazoles 45 , tetrahydropyrazolo[4,3- c ]pyridines 46 etc. have been tried as CB1 receptor antagonists acting peripherally with lower CNS side effects but, unfortunately none of these compounds could make it to the market till date.…”
Section: Introductionmentioning
confidence: 99%
“…Isolated as a white gum (54.6 mg, 0.186 mmol, 74%) from 2n, according to general procedure C: 1 H NMR δ 0.89 (3H, app q, J 7.4 Hz), 1.33 (2H, quint, J 7.9 Hz), 1.48 (9H, s), 1.53 (2H, q, J 7. 6 3-Phenyl-4,5,7,8-tetrahydro-2H-oxepino [4,5-c]pyrazole (3o). Isolated as a white amorphous solid (45.8 mg, 0.214 mmol, 86%) from 2o, according to general procedure C: 1 H NMR δ 2.77 (2H, dd, J 5.0, 4.9 Hz), 2.84 (2H, dd, J 5.0, 4.9 Hz), 3.75 (2H, dd, J 5.1, 5.0 Hz), 3.79 (2H, dd, J 5.0, 4.9 Hz), 7.34 (1H, t, J 7.3 Hz), 7.39 (2H, t, J 7.1 Hz), 7.44 (2H, d, J 7.0 Hz), 10.52 (1H, br); 13…”
Section: N′-cyclobutylidene-4-methylbenzenesulfonohydrazide (1w)mentioning
confidence: 99%
“…However, rather few medicinal chemistry papers have been reported in the literature that describe the application of such models. Some examples include the design of a CB1 receptor antagonist series with reduced central nervous system (CNS) activity by focusing on high Polar Surface Area (PSA) [75], the reduction of P-glycoprotein (P-gp) efflux in b-secretase inhibitors by masking known recognition features [76], and the design of histamine H3 receptor antagonist with reduced hERG using 3D-based models [77].…”
Section: Expert Opinionmentioning
confidence: 99%